Electronic Structures of S/C-Doped TiO2 Anatase (101) Surface: First-Principles Calculations. (2nd June 2014) - Chen, Qili; Liu, Min; He, Kaihua; Li, Bo
Abstract : The electronic structures of sulfur (S) or carbon (C)-doped TiO2 anatase (101) surfaces have been investigated by density functional theory (DFT) plane-wave pseudopotential method. The general gradient approximation (GGA) + U (Hubbard coefficient) method has been adopted to describe the exchange-correlation effects. All the possible doping situations, including S/C dopants at lattice oxygen (O) sites (anion doping), S/C dopants at titanium (Ti) sites (cation doping), and the coexisting of anion and cation doping, were studied. By comparing the formation energies, it was found that the complex of anion and cation doping configuration forms easily in the most range of O chemical potential for both S and C doping. The calculated density of states for various S/C doping systems shows that the synergistic effects of S impurities at lattice O and Ti sites lead a sharp band gap narrowing of 1.35 eV for S-doped system comparing with the pure TiO2 system.